2011
DOI: 10.1063/1.3609069
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime-degrading boron-oxygen centres in p-type and n-type compensated silicon

Abstract: Degradation of minority carrier lifetime under illumination occurs in boron-containing Czochralski silicon of both p- and n-type. In n-Si, the recombination centre responsible for degradation is found to be identical to the fast-stage centre (FRC) known for p-Si, where it is produced at a rate proportional to the squared hole concentration, p2. Holes in n-Si are the excess minority carriers—of a relatively low concentration; hence, the time scale of FRC generation is increased by several orders of magnitude wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 14 publications
9
61
1
Order By: Relevance
“…In 2009, however, Macdonald et al [6] discovered that in p-type material co-doped with boron and phosphorus, where the hole concentration p 0 is smaller than [B], N t * sat was found to be proportional to p 0 and not to [B]. This finding invalidated the model of Schmidt et al, and a new model was later proposed by Voronkov and Falster [7], [8]. In a recent work by Forster et al [9], however, where silicon co-doped with boron and gallium was investigated, it was found that the defect concentration was proportional to [B] instead of p 0 .…”
contrasting
confidence: 43%
See 4 more Smart Citations
“…In 2009, however, Macdonald et al [6] discovered that in p-type material co-doped with boron and phosphorus, where the hole concentration p 0 is smaller than [B], N t * sat was found to be proportional to p 0 and not to [B]. This finding invalidated the model of Schmidt et al, and a new model was later proposed by Voronkov and Falster [7], [8]. In a recent work by Forster et al [9], however, where silicon co-doped with boron and gallium was investigated, it was found that the defect concentration was proportional to [B] instead of p 0 .…”
contrasting
confidence: 43%
“…3). Other groups have reported that degradation typically occurs during the first hours of illumination [8], [15], [16]. In this work we experience that only samples with a hole concentration p 0 above 9 × 10 15 cm -3 saturate within 24 hours.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations